Ant-like stone beetles on the roof of the world. Cephenniini of Nepal and Bhutan (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2017)
The tribe Cephenniini is for the first time reported to occur in the Himalaya Mountains, and 58 species are described: Cephennomicrus arunensis sp. n., Cm. acupunctatus sp. n., Cm. taplejungensis sp. n., Hlavaciellus primitivus sp. n., Cephennodes (s. str.) cavifrons sp. n., C. (s. str.) pampinosus sp. n., C. (s. str.) bagmatianus sp. n., C. (s. str.) popeye sp. n., C. (s. str.) clavodentatus sp. n., C. (s. str.) meredaranus sp. n., C. (s. str.) yangrianus sp. n., C. (s. str.) suturalis sp. n., C. (s. str.) karnaliensis sp. n., C. (s. str.) churtanus sp. n., C. (s. str.) sermathangensis sp. n., C. (s. str.) tipulipes sp. n., C. (s. str.) yeti sp. n., C. (s. str.) inflaticornis sp. n., C. (s. str.) dolakhanus sp. n., C. (s. str.) manangensis sp. n., C. (s. str.) martensi sp. n., C. (s. str.) paramartensi sp. n., C. (s. str.) monolaminatus sp. n., C. (s. str.) thakanus sp. n., C. (s. str.) annapurnaensis sp. n., C. (s. str.) parbatensis sp. n., C. (s. str.) letheanus sp. n., C. (s. str.) myagdiensis sp. n., C. (s. str.) malla sp. n., C. (s. str.) gorkha sp. n., C. (s. str.) tharepatianus sp. n., C. (s. str.) minisulcatus sp. n., C. (s. str.) mustangensis sp. n., C. (s. str.) lalitpuranus sp. n., C. (s. str.) paralalitpuranus sp. n., C. (s. str.) bahrabisensis sp. n., C. (s. str.) bilaminatus sp. n., C. (s. str.) ghorepanianus sp. n., C. (s. str.) cordilaminatus sp. n., C. (s. str.) mangmayanus sp. n. C. (s. str.) bilobatus sp. n., C. (s. str.) gokarnaensis sp. n., C. (s. str.) pseudogokarnaensis sp. n., C. (s. str.) mahisapala sp. n., C. (s. str.) licchavi sp. n., C. (s. str.) gopala sp. n., C. (s. str.) paniporuanus sp. n., C. (s. str.) brachyclavatus sp. n., C. (s. str.) phulchokianus sp. n., C. (s. str.) pokharensis sp. n., C. (s. str.) newar sp. n., C. (s. str.) kusunda sp. n., C. (s. str.) sindhupalchowk sp. n., C. (s. str.) furcatus sp. n., C. (s. str.) penicillipes sp. n., C. (s. str.) sulcatus sp. n., C. (s. str.) kalopanianus sp. n., and C. (s. str.) poonensis sp. n. Cephennodes popeye occurs in Bhutan; all remaining species inhabit Nepal. Four new species groups are established in Cephennodes, and a checklist of all Cephennodes species placed in species groups is given. The presumably plesiomorphic morphological structures of H. primitivus are discussed, and comparative notes on the Himalayan Cephenniini fauna are presented.